2020
DOI: 10.3390/ma13081825
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Surface Integrity of Ti-6Al-4V by Combinations of Additive and Subtractive Manufacturing Processes

Abstract: Additive manufacturing (AM) has recently been accorded considerable interest by manufacturers. Many manufacturing industries, amongst others in the aerospace sector, are already using AM parts or are investing in such manufacturing methods. Important material properties, such as microstructures, residual stress, and surface topography, can be affected by AM processes. In addition, a subtractive manufacturing (SM) process, such as machining, is required for finishing certain parts when accurate tolerances are r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Pores serve as stress risers that are brittle fractures and that increase the susceptibility to failure [ 39 ]. Several studies have shown that advanced tools can help detect faults or other defects that occur in the welding process such as ultrasonic non-destructive testing (NDT) techniques [ 30 ], X-ray CT methods [ 35 , 42 ], and radiographic testing (RT) [ 43 , 44 ]. The slow welding speeds and the welding in the flat position, or uphill in the vertical position, encourage the escape of pores [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pores serve as stress risers that are brittle fractures and that increase the susceptibility to failure [ 39 ]. Several studies have shown that advanced tools can help detect faults or other defects that occur in the welding process such as ultrasonic non-destructive testing (NDT) techniques [ 30 ], X-ray CT methods [ 35 , 42 ], and radiographic testing (RT) [ 43 , 44 ]. The slow welding speeds and the welding in the flat position, or uphill in the vertical position, encourage the escape of pores [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…It may be characterized as a very difficult-to-cut material due to its endurance and relative elongation (6–15%). Moreover, low heat transfer ability causes that the thermal energy does not dissipate easily by conduction, which results in increase of temperatures in the cutting contact area [ 11 ]. A similar situation takes place in the case of cobalt alloys [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reduced wear at lower cutting speeds suggests a longer separation time at lower cutting speeds, which is reduced when the cutting speed is increased. As discussed previously, the main wear in cutting titanium is the adhesion and diffusion wear, caused by the constant friction between tool and workpiece [51]. The in UAT.…”
Section: Tool Wearmentioning
confidence: 90%
“…The length of cut used for all experiments was 15 mm along the axis of the workpiece in the feed direction. The main wear when cutting titanium is the adhesion and diffusion wear [51]. Adhesion is caused by the high cutting temperature and the constant contact and friction between the tool and the workpiece [44].…”
Section: Tool Wearmentioning
confidence: 99%
See 1 more Smart Citation